CHARACTERISTICS OF PATHOLOGIES AND NUTRITION ORGANIZATION IN LENINGRAD DURING GREAT PATRIOTIC WAR - G.L. Mikirtichan (Вопросы современной педиатрии, 2010)
(Voprosy sovremennoi pediatrii — Current Pediatrics. – 2010;9(3):158-162)